Population pharmacokinetics, enzyme occupancy, and 24S‐hydroxycholesterol modeling of soticlestat, a novel cholesterol 24‐hydroxylase inhibitor, in healthy adults - Yin, Wei; Facius, Axel; Wagner, Thomas; Tsai, Max; Asgharnejad, Mahnaz; Lahu, Gëzim; Vakilynejad, Majid (Clinical and translational science, 2023)
Soticlestat is a first‐in‐class, selective inhibitor of cholesterol 24‐hydroxylase (CH24H), which catabolizes cholesterol to 24S‐hydroxycholesterol (24HC) in the brain, in phase III development for Dravet syndrome and Lennox–Gastaut syndrome treatment. This study aimed to develop a model of soticlestat pharmacokinetics (PKs) and pharmacodynamics (PDs) using 24HC plasma concentrations and CH24H enzyme occupancy (EO) time profiles. Subsequently, model‐based simulations were conducted to identify dosing strategies for phase II trials in children and adults with developmental and epileptic encephalopathies (DEEs). Four phase I trials of healthy adults involving oral administration of soticlestat 15–1350 mg were used to develop the mixed‐effect population PK/EO/PD model. The population PK analysis utilized 1727 observations (104 individuals), PK/EO analysis utilized 20 observations (11 individuals), and PK/PD analysis utilized 2270 observations (99 individuals). Optimal dosing strategies were identified from model‐based PK, EO, and PD simulations. The PK/EO/PD model described the observed data well and comprised a two‐compartment model with dose as a covariate on peripheral volume, linear elimination, and intercompartmental clearance. Transit and effect‐site compartments were included to accommodate different dosage forms and the delay between plasma drug concentrations and EO. Model‐based simulations indicated that soticlestat 100–300 mg twice daily may be an optimal adult dosing regimen with weight‐adjusted pediatric dosing strategies identified for evaluation in phase II trials. The population PK/EO/PD model provided understanding of the soticlestat PK/PD relationship with partial delineation of sources of variability, and identified dosing strategies for phase II trials of children and adults with DEEs.